NEP1-40-overexpressing Neural Stem Cells Enhance Axon Regeneration by Inhibiting Nogo-A/NgR1 Signaling Pathway - Zhang, Bi; Wang, Dalin; Li, Xusheng; Yang, Shengsen; Yuan, Haifeng (Current Neurovascular Research, 2021)
Background: Nogo-66 antagonistic peptide (NEP1-40) offers the potential to improve spinal cord injury (SCI). Objective: To explore the effect of NEP1-40 overexpression on neural stem cells (NSCs) regulating the axon regeneration of injured neurons. Methods: We isolated NSCs from brain tissues of pregnant rat fetuses and used Nestin immunofluorescence to identify them. The NEP1-40 overexpressing NSCs were constructed by transfection with the NEP1-40-overexpressing vector. The expression of NSCs differentiation associated markers, including Tuj-1, GFAP, Oligo2, and MBP, were detected by RT-PCR, western blotting, and immunofluorescence. NeuN immunofluorescence staining was used to measure the number of neurons. And western blotting was used to detect the phosphorylation levels of LIMK1/2, cofilin, and MLC-2 and the protein levels of GAP-43, MAP-2, and APP. Results: The NEP1-40 overexpression promoted the expression level of Tuj-1, Oligo2, and MBP, and increased the number of Tuj-1, Oligo2, and MBP positive cells. NEP1-40-overexpressing NSCs (NEP-NSCs) improved NeuN positive cells of co-culture with injured neurons. And NEP-NSCs also increased the protein levels of axon regeneration indicators (GAP-43, MAP-2) and decreased APP protein level. In addition, the phosphorylation level of LIMK1/2, cofilin, and MLC-2 were markedly decreased in NEP-NSCs. Conclusion: NEP1-40 overexpression enhanced the ability of NSCs differentiation into neurons and promoted axon regeneration by inhibiting the Nogo-A/NgR1 signaling pathway. This study provides an alternative gene modified transplantation NSCs for the SCI treatment.
Keywords: spinal cord injury